IMPLEMENTASI PENYETARAAN JABATAN DI PEMERINTAH KOTA YOGYAKARTA - Attanisaa, Gupita Mar; Sugiyanto, Sugiyanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to examine the implementation of job reclassification as part of the bureaucratic simplification policy in the Government of Yogyakarta City. The national bureaucratic simplification policy, mandated through the Regulation of the Minister of Administrative and Bureaucratic Reform No. 25 of 2021 and the President’s instruction in 2019, requires changes in organizational structure, job adjustments, and work systems across government institutions, including the Yogyakarta City Government. This research employs a qualitative method with a descriptive approach through observation, in-depth interviews, and documentation. Data analysis is conducted using the model of Miles, Huberman, and Saldana, which includes data condensation, data display, and conclusion drawing. The findings indicate that the implementation of job reclassification was carried out through three main stages: structural simplification, conversion of administrative positions into functional positions, and adjustments to a cross-sector team-based work system. The Yogyakarta City Government reclassified 177 officials in 2021 and continued the process in 2022 with an additional five officials. The study identifies several challenges, including the limited readiness of human resources, concerns about credit points, mismatch between technical competencies and job requirements, and worries related to income changes. Nevertheless, the reclassification also provides benefits such as improved organizational efficiency, faster decision-making, greater work system flexibility, and strengthened collaborative work culture. Overall, job reclassification in the Yogyakarta City Government has been carried out effectively and aligns with national bureaucratic reform objectives. However, further efforts are required to enhance ASN competencies, develop more accurate functional position planning, and strengthen the work system to ensure that the goals of bureaucratic simplification can be fully achieved. ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana implementasi penyetaraan jabatan dalam rangka penyederhanaan birokrasi di Pemerintah Kota Yogyakarta. Kebijakan nasional penyederhanaan birokrasi yang ditetapkan melalui Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Nomor 25 Tahun 2021 dan instruksi Presiden tahun 2019 menuntut perubahan struktur, penyesuaian jabatan, serta sistem kerja di berbagai instansi pemerintah, termasuk Pemerintah Kota Yogyakarta. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif melalui teknik observasi, wawancara mendalam, serta dokumentasi. Analisis data dilakukan menggunakan model Miles, Huberman, dan Saldana yang mencakup kondensasi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi penyetaraan jabatan dilaksanakan melalui tiga tahapan utama, yaitu penyederhanaan struktur organisasi, konversi jabatan administrasi menjadi jabatan fungsional, serta penyesuaian sistem kerja berbasis tim lintas bidang. Pemerintah Kota Yogyakarta menyetarakan 177 pejabat pada tahun 2021 dan melanjutkan proses tersebut pada tahun 2022 dengan tambahan lima pejabat. Penelitian menemukan beberapa hambatan seperti keterbatasan kesiapan sumber daya manusia, kecemasan terkait angka kredit, ketidaksesuaian kompetensi teknis, serta kekhawatiran tentang pendapatan. Meskipun demikian, penyetaraan jabatan juga memberikan manfaat berupa peningkatan efisiensi kerja, percepatan proses pengambilan keputusan, fleksibilitas sistem kerja, dan penguatan budaya kolaboratif. Secara keseluruhan, penyetaraan jabatan di Pemerintah Kota Yogyakarta telah berjalan cukup baik dan selaras dengan arah reformasi birokrasi nasional. Namun masih diperlukan peningkatan kompetensi ASN, perencanaan formasi jabatan fungsional yang lebih matang, serta penguatan sistem kerja agar tujuan penyederhanaan birokrasi dapat tercapai secara optimal.